Foucault Comes to Bakur: Sovereign Power and Collective Punishment (Glocalism: Journal of Culture, Politics and Innovation, 2016)
The Solution Process in Turkey has come to an abrupt end and along with it came an unprecedented violence in Bakur (Northern Kurdistan). This paper argues that the violence ravaging the region – especially in those areas where curfews have been declared – can be considered as a practice of punishment that is being employed indiscriminately. In line with this thought, the paper adopts a Foucauldian approach for compre- hending the motivations behind the practice of collective punishment. In doing so, the paper revolves around the concepts of sovereign power and punishment introduced and argued by Michel Foucault. The paper argues that success of a pro-Kurdish party (HDP) in June 7 elections and following declarations of self-rule in the region constituted an obstacle in Erdoğan’s desire for presidency but more importantly he took it as an act of dissent to his sovereign will. As can be seen in the functioning of sovereign power, he therefore punishes those people who are HDP’s main constituent while making an example out of them for potential challengers to his sovereign will.
Keywords: Northern Kurdistan; sovereign power; collective punishment; Turkey; Foucault